Consumer Satisfaction and Consumer Loyalty Analysis (Case Study of Rama Palu) - Hilda Monoarfa (JURISMA : Jurnal Riset Bisnis & Manajemen, 2013)
This is a research which observes the relationship between customer satisfaction and their loyalty to Rama Hotel. The customer satisfaction is measured through some attributes such as, attributes related to the product, attributes related to the service, and attributes related to the purchase. Meanwhile, the loyalty of its brand is measured through habitual behaviour, switching cost, satisfaction, liking of the brand and commitment. The result of the research reveals that customer satisfaction levels to Rama Hotel tends to be good. Some attributes still have a variety of high grade, and there is a positive causal influence that is significant between the customer satisfaction and the loyalty of the brand. Thus, the result of the research is relevant and at the same time supports the theory of brand loyalty.Keywords: satisfaction, brand loyalty.